2018
DOI: 10.3390/met8090671
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Process and Product Metallurgy in Niobium Bearing Steels

Abstract: A review of the technological integration of both the process and physical metallurgical advancements of value-added niobium (Nb) microalloyed thermo-mechanical controlled process (TMCP) steels have evolved into the development of higher quality steels for more demanding end user requirements. The connection of process and physical metallurgy is evolving through the integration of research that is aimed at improving product quality. However, often the connection of the process metallurgical parameters is not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Niobium is a metal that is used in metallurgy to augment the properties of different metals [ 99 ]. The use of niobium pentoxide (Nb 2 O 5 ) related to dental applications has risen recently.…”
Section: Bioactive Inorganic Fillersmentioning
confidence: 99%
“…Niobium is a metal that is used in metallurgy to augment the properties of different metals [ 99 ]. The use of niobium pentoxide (Nb 2 O 5 ) related to dental applications has risen recently.…”
Section: Bioactive Inorganic Fillersmentioning
confidence: 99%
“…The present Special Issue on Advances in Microalloyed Steels includes two review papers [1,2] and nine research papers [3][4][5][6][7][8][9][10][11]. In all of them, different combinations of microalloying elements are analyzed in terms of process, microstructure, and mechanical property modification.…”
Section: Contributionsmentioning
confidence: 99%
“…The alternatives in microalloying are clearly reflected in terms of the grades studied in the different papers. Nb is present in many of them [1,2,5,7,8,10,11], alone or in combination with Mo [2,5,10], Ti [8], and V [10]. Two papers deal with Ti-Mo combinations [6,9], and the last two articles analyze the addition of V [4] and Al [3] as microalloying elements.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact was unusual, since the finishing stage had started around 940-970°C, well below the of T nr experimentally determined by a multiple hot torsion test for a similar steel, 1070°C [13], according to the procedure proposed by Boratto et al [14], as shown in Figure 1. It should be noted that the difference between T nr measured in the laboratory and the finishing start temperature adopted in the industrial controlled rolling was advocate its replacement by Nb microadditions, which have been done with good results both in technical and economic terms [2]. Other advantages resulting from the lowering of the Mn content, these already known for a long time, are the reduction of the load of ferroalloys in the ladle and the consequent loss of heat by the liquid steel and lower contamination by P, as well minimization of central segregation intensity in slabs and microstructural banding in the final products [3].…”
Section: Introductionmentioning
confidence: 99%